2017
DOI: 10.1128/mcb.00457-16
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Methylation by PRMT1 Regulates Muscle Stem Cell Fate

Abstract: Quiescent muscle stem cells (MSCs) become activated in response to skeletal muscle injury to initiate regeneration. Activated MSCs proliferate and differentiate to repair damaged fibers or self-renew to maintain the pool and ensure future regeneration. The balance between self-renewal, proliferation, and differentiation is a tightly regulated process controlled by a genetic cascade involving determinant transcription factors such as Pax7, Myf5, MyoD, and MyoG. Recently, there have been several reports about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 44 publications
9
62
0
Order By: Relevance
“…IGF1 is known to increase embryonic myoblast proliferation, but Igf1 mRNA levels tend to be higher during myogenic differentiation . Increased mRNA levels of Prmt1 in response to releasate administration are in line with previous data reporting that arginine methylation by Prmt1 regulates muscle stem cell fate and it is important for myoblast fusion . Taken together, these data suggest that the observed effects on myoblast proliferation by platelet releasate may be at least in part mediated by the PDGF and VEGF growth factors.…”
Section: Discussionsupporting
confidence: 89%
“…IGF1 is known to increase embryonic myoblast proliferation, but Igf1 mRNA levels tend to be higher during myogenic differentiation . Increased mRNA levels of Prmt1 in response to releasate administration are in line with previous data reporting that arginine methylation by Prmt1 regulates muscle stem cell fate and it is important for myoblast fusion . Taken together, these data suggest that the observed effects on myoblast proliferation by platelet releasate may be at least in part mediated by the PDGF and VEGF growth factors.…”
Section: Discussionsupporting
confidence: 89%
“…The absence of PRMT1 in the Pax7-Cre mouse model leads to hypomethylation of Eya1 and subsequent decrease of Eya1 binding to the MyoD promoter. MyoD levels decrease in PRMT1 null muscle stem cells, impairing their differentiation, and increasing their expansion in vivo, ultimately leading to an increase of Pax7-positive cells with disrupted regeneration (Blanc et al, 2016b) (Figure 4).…”
Section: Muscular Systemmentioning
confidence: 99%
“…3A). Indeed, we detected Flag‐tagged EYA1 with ASYM26, an antibody that recognizes asymmetric dimethyl‐arginine (20) in anti‐Flag immuno‐precipitations (Fig. 3 B ).…”
Section: Resultsmentioning
confidence: 98%
“…A more recent study reported that PRMT1 methylates EYA1 and that loss of PRMT1 function in muscle stem cells leads to reduced transcription of SIX1/EYA1 target genes (such as MyoD and SIX1) due to disruption of EYA1 recruitment at these genes. The authors propose that PRMT1‐mediated methylation of EYA1 may promote EYA1 recruitment at SIX1/EYA1 target genes and subsequent transcriptional activation (20). On the basis of these findings and those of our previous study showing that PRMTs facilitated the recruitment of CBP‐containing transcriptional coactivators during transcriptional activation (21), it is conceivable that PRMT1 may coordinate both the phosphatase and transactivation activities of EYA by arginine methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation